Osteossarcoma osteoblástico produtivo em cão: relato de caso - SILVA, Julia Gomes Pontes da (2024)
An 8-year-old mixed breed dog, weighing 8.45kg, presented hypertrophic lesions in the oral cavity, in the left maxillary region, with 1 month of evolution, with the characteristics of an irregular, adherent, ulcerated mass. Size was not measured. She had the lesions removed in consultation with an external veterinarian, and after a week it showed recurrence and growth. At the consultation after removal, the animal was alert and responsive despite the difficulty breathing and pain presented. Tissue was collected for histopathological examination, where neoplastic proliferation was identified, with characteristics that confirmed the diagnosis of Productive Osteoblastic Osteosarcoma. Her condition worsened after diagnosis and was sent for euthanasia. After euthanasia, a post-mortem x-ray was performed where no obvious point of metastasis was observed. Osteosarcomas are malignant mesenchymal neoplasms of bone origin that have a great aggressive potential, therefore, bone destruction and periosteal and endosteal reactions are common in affected bones. Bones of the appendicular skeleton are more affected than those of the axial skeleton and the infiltrative nature of the tumor can lead to the involvement of adjacent and distant organs, through hematogenous dissemination, especially to the lungs. Therefore, metastases must be considered and investigated. Immunohistochemical analysis is suggested to confirm tumor histogenesis.